Reversing Epithelial Polarity in Pluripotent Stem Cell-Derived Intestinal Organoids - Kakni, Panagiota; López-Iglesias, Carmen; Truckenmüller, Roman; Habibović, Pamela; Giselbrecht, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
The inner surface of the intestine is a dynamic system, composed of a single layer of polarized epithelial cells. The development of intestinal organoids was a major breakthrough since they robustly recapitulate intestinal architecture, regional specification and cell composition in vitro. However, the cyst-like organization hinders direct access to the apical side of the epithelium, thus limiting their use in functional assays. For the first time, we show an intestinal organoid model from pluripotent stem cells with reversed polarity where the apical side faces the surrounding culture media and the basal side faces the lumen. These inside-out organoids preserve a distinct apico-basolateral orientation for a long period and differentiate into the major intestinal cell types. This novel model lays the foundation for developing new in vitro functional assays particularly targeting the apical surface of the epithelium and thus offers a new research tool to study nutrient/drug uptake, metabolism and host-microbiome/pathogen interactions.